2020
DOI: 10.3390/su12083208
|View full text |Cite
|
Sign up to set email alerts
|

Urban Network and Regions in China: An Analysis of Daily Migration with Complex Networks Model

Abstract: This paper analyzed urban network and regions in China using a complex network model. Data of daily migration among 348 prefectural-level cities from the Baidu Map location-based service (LBS) Open Platform were used to calculate urban network metrics and to delineate boundaries of urban regions. Results show that urban network in China displays an obvious hierarchy in terms of attracting and distributing population and controlling regional interaction. Regional integration has become increasingly prominent, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 30 publications
(32 reference statements)
0
13
0
Order By: Relevance
“…Sustainability 2021, 13, x FOR PEER REVIEW 3 of 15 spatial structure. The Results and Discussion section presents the experiments and results, and discusses next steps.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sustainability 2021, 13, x FOR PEER REVIEW 3 of 15 spatial structure. The Results and Discussion section presents the experiments and results, and discusses next steps.…”
Section: Methodsmentioning
confidence: 99%
“…The advent of the big data era has put forward new ideas for the study of urban spatial patterns. Currently, data based on location-based service (LBS) technology are the most widely used data in urban research, such as bus card records, taxi trajectory data, mobile phone call records, and login data based on social media [10][11][12][13][14]. These data can be interpreted as a description of the city, and their mining and analysis can lead to a more people-oriented urban spatial pattern [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Since "networks" are becoming a new form of and new research paradigm for intercity spatial structure, a complex network constructed using the interaction among entities of a complex system 4 Complexity provides a new means of studying network complexity. In recent years, the complex network approach has been widely used in urban economic network research and has achieved impressive results [68,69]. Researchers used complexity theory and tools that directly describe the topology of complex networks, e.g., the degree centrality, average path length, and clustering coefficient, to study the nodes and edges of urban economic networks [27,70] (Figure 2).…”
Section: Data Processing and Researchmentioning
confidence: 99%
“…The dynamic characteristics and patterns of population mobility between cities are largely influenced by the temporal and spatial dimensions of mobility [45]. Population mobility occurs in different periods of time, such as weekdays, weekends, May Day holidays, and Spring Festival holidays, and tends to show the variety and diversity of population mobility characteristics and patterns due to the differences in the identity of mobility groups-time utilization characteristics, social and environmental conditions and constraints, and mobility for purposes such as work, entertainment, social interaction, and returning to one's hometown [46,47]. The results of scholars researching relevant countries and regions have shown that people mainly move across regions on weekdays, but their destinations are relatively concentrated, and weekends show a near-regional movement but a scattered pattern [48].…”
Section: Spatial-temporal Heterogeneity Of Population Mobilitymentioning
confidence: 99%